Moderating Influence of Employee Competence on the Relationship between Employee Work Values Orientation and Job Performance in the Motor Vehicle Industry in Kenya - Wasike, Fredrick; K’Obonyo, Peter; Muindi, Florence (Archives of Business Research, 2024)
The objective of the study was to establish the moderating influence of employee competence in the relationship between employee work values orientation and employee job performance in the motor vehicle industry in Kenya. This relationships was tested using corresponding null hypothesis. This study was based on competence motivation theory. The objective of the study was to eastablish the moderating influence of employee competence in the relationship between employee work values orieontation and employee pefrmance. Descriptive cross sectional survey was used in the study. The study had a population of 2,895 employees out of which a sample of 351 respondents were randomly chosen for data collection. Data was collected by use of structured questionnaires that were dropped and picked back while others were scanned and emailed back. Data was analyzed using regression models. Test findings showed that employee competence moderated the ralationship between work values orientation and employee job performance,. The significant findings implied that the hypothesis was rejected, and the study objective was positively determined. The study outcomes significantly contributed to theory, policy and practice of work values orientation and its influence on employee job performance. The limitation of the study comprised respondents’ attitude and subjectivity that may have crept in due to bias in choosing suitable responses, however the use of structured questionnaires reduced personal or subjective ways of responding to statements posed. The study suggested that a further study be done using similar variables on a longitudinal design for generalizability of results. Further, the study recommended that the motor vehicle industry adopts work values orientation and employee competence as joint variables that significantly improve employee job performance.